2008
DOI: 10.1128/iai.00365-08
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Depletion ReducesHelicobacter pyloriCagA Translocation and CagA-Induced Responses in AGS Cells

Abstract: Infection with Helicobacter pylori cagA-positive strains is associated with gastritis, ulcerations, and gastric cancer. CagA is translocated into infected epithelial cells by a type IV secretion system and can be tyrosine phosphorylated, inducing signal transduction and motogenic responses in epithelial cells. Cellular cholesterol, a vital component of the membrane, contributes to membrane dynamics and functions and is important in VacA intoxication and phagocyte evasion during H. pylori infection. In this inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
123
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(132 citation statements)
references
References 67 publications
9
123
0
Order By: Relevance
“…The internalized H. pylori bacteria are found in LAMP1-containing vacuoles. The CagA protein can be translocated to the plasma membrane and form rafts with the invading H. pylori (12).…”
Section: Discussionmentioning
confidence: 99%
“…The internalized H. pylori bacteria are found in LAMP1-containing vacuoles. The CagA protein can be translocated to the plasma membrane and form rafts with the invading H. pylori (12).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that virulence factors of H. pylori associate with cholesterol-rich microdomains of the plasma membrane, commonly termed lipid rafts (34). These domains not only are enriched in cholesterol but also contain sphingolipids and proteins (53) and have been reported to be sites utilized by bacteria to interact with host cells (1) or as portals of entry by which bacteria enter these cells (29,33).…”
mentioning
confidence: 99%
“…Furthermore, disruption of cholesterol-rich microdomains using cholesterol-depleting agents such as methyl-␤-cyclodextrin (M␤CD) was shown to significantly reduce the internalization of the vacuolating cytotoxin (VacA) into target cells (49) and to inhibit the ability of the toxin to induce cell vacuolation (31,48). Moreover, Lai et al reported that cholesterol-rich microdomains are also crucial for efficient TFSSmediated CagA translocation by H. pylori, as CagA-induced cellular responses, including the cell-scattering phenotype and IL-8 production, were found to be reduced in M␤CD-treated cells (34).…”
mentioning
confidence: 99%
“…Host membrane cholesterol most likely contributes by providing a sturdy rigid membrane for docking of the needle-like apparatus, which can then inject toxin CagA into the cytoplasm of host cells. In support of this, Lai et al 86 showed that cholesterol depletion in host cells prevents translocation and phosphorylation of the CagA toxin, as well as its cellular functions including induction of the motile "hummingbird" phenotype and IL-8 secretion. Interestingly, the same phenotypes are seen with the encoded by the pgl locus, H. pylori only seems to possess a homolog to PglK, which it encodes in the wzk gene.…”
Section: Helicobacter Pylori and Cholesterolmentioning
confidence: 93%
“…80 Further, infection with wild-type H. pylori is known to cause clustering of lipid rafts at sites of host-pathogen contact, thereby concentrating local cholesterol levels. 86 Some of this cholesterol is extracted from the host cell membrane and converted into cholesteryl-α-glucosides. However, the pathogen seems to maintain a balance with the host membrane, as host cell cholesterol-rich domains are also required for proper assembly and function of the bacterial T4SS.…”
Section: Helicobacter Pylori and Cholesterolmentioning
confidence: 99%